2009
DOI: 10.1016/j.neuroimage.2009.05.087
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study on the interaction and dissociation between expectation of pain relief and acupuncture treatment

Abstract: It is well established that expectation can significantly modulate pain perception. In this study, we combined an expectancy manipulation model and fMRI to investigate how expectation can modulate acupuncture treatment. Forty-eight subjects completed the study. The analysis on two verum acupuncture groups with different expectancy levels indicates that expectancy can significantly influence acupuncture analgesia for experimental pain. Conditioning positive expectation can amplify acupuncture analgesia as detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 67 publications
(128 reference statements)
4
130
1
1
Order By: Relevance
“…64 Neuroscience studies have confirmed that sham needling is not physiologically inert. 65,66 Since the first innovative invention of the placebo acupuncture needle was introduced in 1998, 67 attempts at designing a perfect placebo acupuncture device have been ongoing. However, thus far, no optimal placebo for acupuncture research seems to exist.…”
Section: Strength and Limitation Of This Studymentioning
confidence: 99%
“…64 Neuroscience studies have confirmed that sham needling is not physiologically inert. 65,66 Since the first innovative invention of the placebo acupuncture needle was introduced in 1998, 67 attempts at designing a perfect placebo acupuncture device have been ongoing. However, thus far, no optimal placebo for acupuncture research seems to exist.…”
Section: Strength and Limitation Of This Studymentioning
confidence: 99%
“…240 Other functional magnetic resonance studies have confirmed that expectancy can significantly influence acupuncture analgesia. [249][250][251] A recent study concluded that patients with a high degree of dispositional optimism and low state anxiety were particularly receptive to placebo responses. 252 It is likely that similar issues must be considered when designing dry needling studies.…”
Section: Dry Needling and Trigger Pointsmentioning
confidence: 99%
“…why strong expectations can reverse placebo conditioning (Benedetti et al, 2003) and (3.) why analgesia following acupuncture can be regionally specific (Kong et al, 2009). Future studies therefore have to carefully assess, whether 'imagery proneness' may be an underestimated mediator of placebo effects and other phenomena of biased perception.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%